Stable oxygen and carbon isotope records of coral 18SM-C2, northeast Brazil - Pereira, Natan S; Clarke, Leon J; Chiessi, Cristiano Mazur; Kilbourne, Hali; Crivellari, Stefano; Cruz, Francisco William; Liu, Yu; Shen, Chuan-Chou; Kikuchi, Ruy Kenji P; Pinheiro, Barbara; Longo, Guilherme; Sial, Alcides; et al. (PANGAEA, 2025)
This dataset comprises stable oxygen and carbon isotope records derived from a coral core of the species Siderastrea stellata (labled 18SM-C2), collected from the Maracajaú Reef (5.35°S, 35.24°W) along the northeastern coast of Brazil. A total of 768 isotopic measurements were performed on coral 18SM-C2, with powder samples acquired at a resolution of 0.4 mm, covering a temporal span of 93 years. δ18O and δ13C values were calibrated against the Vienna Pee Dee Belemnite (VPDB) standard using NBS19, with an analytical precision better than ±0.07 for δ18O and ±0.05‰ for δ13C (±1σ, n = 141). Additionally, annual growth rate data for 18SM-C2 are provided, determined by counting density bands visible in X-ray radiograph.
Keywords: Coral; South Altantic; Stable carbon and oxygen isotopes